2016
DOI: 10.1177/1557988316631624
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Consequences of Finasteride: Fool’s Gold

Abstract: Androgenetic alopecia, the gradual, progressive loss of hair frequently results in psychological despair, in part related to changes in self-image. Current androgenetic alopecia treatments are limited to hair transplantation and medications that inhibit dihydrotestosterone, a potent androgen associated with follicular micronization. Users of finasteride, which prevents dihydrotestosterone production, report serious physical and emotional adverse effects, collectively known as post-finasteride syndrome. Psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 39 publications
1
23
2
4
Order By: Relevance
“…In addition, based on the BAI results, 16 subjects reported moderate anxiety and 17 scored a potential cause for concern [32]. A noteworthy finding in this study is that the authors postulated that subjects would score high on the neuroticism personality domain according to the TIPI, but found that this was not the case as subjects were extroverted, agreeable, emotionally stable, and open to experiences.…”
Section: Resultscontrasting
confidence: 44%
See 2 more Smart Citations
“…In addition, based on the BAI results, 16 subjects reported moderate anxiety and 17 scored a potential cause for concern [32]. A noteworthy finding in this study is that the authors postulated that subjects would score high on the neuroticism personality domain according to the TIPI, but found that this was not the case as subjects were extroverted, agreeable, emotionally stable, and open to experiences.…”
Section: Resultscontrasting
confidence: 44%
“…A noteworthy finding in this study is that the authors postulated that subjects would score high on the neuroticism personality domain according to the TIPI, but found that this was not the case as subjects were extroverted, agreeable, emotionally stable, and open to experiences. A total of 55% (n = 53) of subjects had an established psychiatric diagnosis prior to initiating finasteride therapy, while 28.8% (n = 27) had a first-degree relative with a mental health disorder [32]. The authors concluded that pre-existing mental health disorders among finasteride users may put this subset of users at an increased risk of developing emotional disorders caused by finasteride therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recently published pilot study using a survey method to characterize psychological (and other) symptoms in men who used finasteride to treat MPB, the cohort reported high rates of psychological symptoms ( Ganzer et al, 2015 ); these effects are much like what we report here using a different approach. Moreover, a recent report has corroborated and extended these results to assess specifically mood symptoms ( Ganzer & Jacobs, 2016 ). Further, in a clinical study, significantly increased depression symptoms and suicidality were reported by three-quarters of the subject group that had discontinued finasteride, compared to about 10% of the control group ( Irwig, 2012a ).…”
Section: Discussion: Recommendations For Further Study and Categorizamentioning
confidence: 61%
“…sought treatment for persistent adverse effects after the discontinuation of finasteride, 1 mg, there were high rates of depression, and suicidal thoughts, although there is an obvious selection bias in these studies, and some of these findings may be explained by preexisting psychiatric problems. 33,34,52 Strengths and Limitations…”
Section: Discussionmentioning
confidence: 99%